Back to the Future: The Architecture of Entertainment. (26th October 2021) - Cook, Peter
Abstract: Throughout Peter Cook 's long and influential career, he has been at the epicentre of architectural education and architectural speculation. Here he remembers some of the genesis moments of entertainment architecture and its characters. Using examples from STUFISH's oeuvre he asserts that entertainment architecture is Architecture with a capital 'A' and at least as relevant as any of the discipline's other manifestations.